Improved outcome after emergency surgery for cancer of the large intestine - Runkel, Norbert; Hinz, Ulf; Lehnert, Thomas; Buhr, Heinz J.; Herfarth, Christian (The British journal of surgery, 1998)
Emergency surgery for colorectal cancer has become more aggressive and radical over the past decade. This retrospective review analyses the impact on outcome.The results of emergency surgery within 24 h of admission were compared between 1982 and 1987 (77 patients) and 1988 and 1993 (75 patients). Patient and tumour characteristics were similar in both groups.Right colonic obstruction or perforation was treated by primary resection and anastomosis in 11 of 12 patients before 1988 and in all 19 patients thereafter. Primary resection was also the treatment of choice for perforated cancer of the left colon and rectum before 18 of 20) and after (20 of 21) 1988. The rate of primary resection for obstructing cancer of the left colon and rectum increased from 17 of 45 to 30 of 35. One-stage resections for obstructing cancer were performed in ten of 45 and 22 of 35 patients before and after 1988 respectively. The overall mortality rate declined from 14 of 77 to three of 75 after 1988 (P < 0·01). The rate of radical lymphadenectomy rose from six of 46 patients to 42 of 69 after 1988. The 3-year survival rate increased from 50 to 74 per cent (P < 0·05).The data support further efforts towards improving the immediate and late outcome of emergency surgery in complicated colorectal cancer.
Gesehen am 22.10.2025